2020
DOI: 10.3390/nu12113263
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Dietary Diversity on the Risk of Disability in Activities of Daily Living in Adults: A Prospective Cohort Study

Abstract: Disability in activities of daily living (ADL) is common in elderly people. Dietary diversity is associated with several age-related diseases. The evidence on dietary diversity score (DDS) and ADL disability is limited. This study was based on the China Health and Nutrition Survey. Prospective data of 5004 participants were analyzed. ADL disability was defined as the inability to perform at least one of the five self-care tasks. Cox proportional regression models were conducted to estimate the association of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
(44 reference statements)
0
9
1
Order By: Relevance
“…Given that dietary habits could change over time, food consumption assessment at a single time point possibly results in nondifferential bias. Nevertheless, in nutritional epidemiology, it is always assumed that an adult's dietary habits would not change dramatically during a short period [25]; also, it has been indicated that the methods using baseline diet data only generally result in a weaker association than do these using the cumulative averages [49]. Second, all individuals included in our study were American adults aged 55e74 years; moreover, 90.9% of them were non-Hispanic white; 36.6% were college students; and 51.0% were current or former smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Given that dietary habits could change over time, food consumption assessment at a single time point possibly results in nondifferential bias. Nevertheless, in nutritional epidemiology, it is always assumed that an adult's dietary habits would not change dramatically during a short period [25]; also, it has been indicated that the methods using baseline diet data only generally result in a weaker association than do these using the cumulative averages [49]. Second, all individuals included in our study were American adults aged 55e74 years; moreover, 90.9% of them were non-Hispanic white; 36.6% were college students; and 51.0% were current or former smokers.…”
Section: Discussionmentioning
confidence: 99%
“…DDS is more accessible and simpler for middle-aged and older people since only have to consider the frequency of food intake [10,11]. As the widely-used tool to evaluate diet quality, it has been validated among different populations and confirmed to be associated with several age-related diseases, such as diabetes [12,13], anxiety [14], disability [15], and all-cause mortality [16,17]. To our knowledge, there have been limited studies conducted thus far to investigate the relationship between DDS and MCI.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dietary habits of individuals do not change dramatically and studies using a single measurement of dietary information often yield weaker association indicators. 44 This study, despite using one‐time measure, provides a strong association, suggesting that low‐fat dairy products have a definitive preventive impact against lung cancer and are even more significant than the results presented in this study.…”
Section: Discussionmentioning
confidence: 49%